PHOTOVOLTAIC PERFORMANCE OF SOLAR CELLS ENHANCED BY TIO₂ AND ZNO NANOPARTICLE LAYERS - Arooj Fatima; Mukarram Ali; Abdul Sattar; Maria Urooj; Muhammad Hisham Al Nasir; Asad Riaz; Mati Ullah; Maneeb Ur Rehman; Mansoor Inayat khan; Muhammad Asad Ali (Spectrum of Engineering Sciences, 2025)
The growing demand for renewable energy has intensified research into enhancing the efficiency of solar cells. This study investigates the photovoltaic performance of solar cells improved with titanium dioxide (TiO₂) and zinc oxide (ZnO) nanoparticle layers. These nanomaterials were selected for their unique properties, such as high charge carrier mobility, tunable bandgap, and superior light absorption, which address key challenges like electron-hole recombination and limited visible spectrum absorption in conventional solar cells. TiO₂ and ZnO nanoparticles were synthesized and deposited onto fluorine-doped tin oxide (FTO) substrates using spin coating, followed by annealing to optimize crystallinity and adhesion. The fabricated solar cells were characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), UV-Vis spectroscopy, and current-voltage (I-V) measurements. XRD confirmed the high crystallinity and phase purity of the nanoparticles, while SEM revealed uniform morphology and reduced grain boundaries, enhancing charge transport. UV-Vis spectra demonstrated improved light absorption in both UV and visible regions. I-V measurements showed a significant boost in power conversion efficiency (PCE), reaching 14.57% for cells with optimized TiO₂/ZnO layers, attributed to enhanced charge separation and reduced recombination. The results highlight the synergistic effect of TiO₂ and ZnO nanoparticles in improving solar cell performance, offering a promising pathway for the development of next-generation photovoltaic devices. This research highlights the potential of nanomaterials in advancing solar energy technologies to meet global energy demands sustainably.